EFFECTS OF THE DOW JONES INDEX AND RUPIAH EXCHANGE RATE ON THE 2013-2017 COMPOSITE STOCK PRICE INDEX - Amanah, Amanah (Universitas Negeri Semarang, 2019)
This study aims to examine the effect of the Dow Jones Index (X1) with the Composite Stock Price Index (Y) in Indonesia and the influence between the rupiah exchange rate (X2) on the Composite Stock Price Index (Y) in Indonesia in the period 2013-2017. In statistical testing, the number 0.2212 was obtained related to the influence of X1 and Y, which means that every change in one unit of X1 can lead to changes in Y by 22 %, and means there is a weak influence between variables X1 and Y partially, while for the purpose of X2 and Y obtained the number 0.6531, which means that every change in unit X2 can result in a change in Y by 65 %, which means there is a high influence between variables X2 and Y partially. In the F test, P Value is generated 0.00000 <0.05, which means there is a simultaneous influence between the two independent variables on the dependent variable, while the Determination Coefficient results in R-Squared value of 0.975966, which means a set of predictor variables in the model can explain the response variable 97 %, while the rest is explained by other variables outside the model under study.  Penelitian ini bertujuan untuk menguji pengaruh Indeks Dow Jones (X1) dengan Indeks Harga Saham Gabungan (Y) di Indonesia dan pengaruh antara nilai tukar rupiah (X2) terhadap Indeks Harga Saham Gabungan (Y) di Indonesia pada periode 2013-2017. Dalam pengujian statistik, angka 0,2212 diperoleh terkait dengan pengaruh X1 dan Y, yang berarti bahwa setiap perubahan dalam satu unit X1 dapat menyebabkan perubahan Y sebesar 22%, dan berarti ada pengaruh yang lemah antara variabel X1 dan Y sebagian, sedangkan untuk keperluan X2 dan Y diperoleh angka 0,6531, yang berarti bahwa setiap perubahan dalam unit X2 dapat menghasilkan perubahan Y sebesar 65%, yang berarti ada pengaruh yang tinggi antara variabel X2 dan Y secara parsial. Dalam uji F, Nilai P dihasilkan 0,00000 <0,05, yang berarti ada pengaruh simultan antara dua variabel independen pada variabel dependen, sedangkan Koefisien Determinasi menghasilkan nilai R-Squared 0,975966, yang berarti satu set variabel prediktor dalam model dapat menjelaskan variabel respon 97%, sedangkan sisanya dijelaskan oleh variabel lain di luar model yang diteliti.